Pengaruh Pemasaran Online, Merek, dan Kualitas Produk terhadap Pembelian Masker Pada Pengguna Situs Online Shopee: (Studi pada Mahasiswa FIK Universitas Kusuma Husada Surakarta) - Murtopo, Agus Suryo; Kismanto, Joko (Valid: Jurnal Ilmiah, 2024)
Purchasing decision is the culmination of consumer behavior, in which finally, the consumers will do purchase having passed through some stages of consumer behavior. In this research, consumer behaviors being the variable of research are price, brandtrust, and online service, while the variable affected is purchasing decision. Purchasing decision implemented online is, of course, more complex than the one implemented directly, in which buyers interact face to face with the sellers. The objective of research is to analyze the effect of online marketing, brand, and product quality on purchasing decision made in online purchase in the consumers on the shopee online site in Surakarta. Questionnaire was used as an instrument of collecting data in this research and SPSS version 24 software was used to analyze data. Data analysis was carried out using a multiple linear regression. The result of research shows that online marketing, brand, and product quality affect the decision of purchasing Mask positively and significantly, either partially or simultaneously.